Kadar Pendidikan Multikultural pada Buku Teks Pelajaran Agama SMA Kurikulum 2013: Tanggapan Agama terhadap Isu Multikulturalitas - Viktorahadi, R. F. Bhanu (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2019)
Renouncing the reality of plurality and multiculturality can provoke religious violence and social conflicts. The emergence of violence might have been one of the consequences of the deteriorating role of education, particularly the religious education, in the society. As part of the national education system in Indonesia, religious education bears on its shoulders the responsibility to propagate the values of plurality and multiculturality. It also disseminates other related values such as inclusiveness and tolerance, which are of paramount significance in building a society characterised by peace, harmony, solidarity, and respect to people of different cultures and religions. It is therefore an important role of Islamic Religious Education and Catholic Religious Education in Indonesia to cultivate ways of thinking that support plurality and multiculturality. This article analyses degrees of integration of plurality and multiculturality understanding in the 2013 curricula of Islamic Religious Education and Catholic Religious Education in high schools. The students’ better understanding of plurality and multiculturality can help them promote the above mentioned values as part of God-given reality in the society.